Once‐weekly subcutaneous semaglutide treatment for persons with type 2 diabetes: Real‐world data from a diabetes out‐patient clinic. Issue 10 (4th August 2021) - Hansen, Katrine B.; Svendstrup, Mathilde; Lund, Asger; Knop, Filip K.; Vilsbøll, Tina; Vestergaard, Henrik
Abstract: Aims: The once‐weekly administered glucagon‐like peptide 1 (GLP‐1) receptor agonist (GLP‐1RA) semaglutide, has, in clinical trials, demonstrated significant reductions in glycated haemoglobin A1c (HbA1c ) and body weight in persons with type 2 diabetes. We evaluated the real‐world clinical effects of semaglutide once weekly in a hospital‐based diabetes out‐patient clinic. Methods: This retrospective observational cohort study included persons with type 2 diabetes ( n = 119) on a broad range of antidiabetic medicine: GLP‐1RA naïve persons ( n = 37) and GLP‐1RA‐experienced persons ( n = 82). Person characteristics at inclusion: age [median (quartiles)]: 65 (57, 72) years; body weight 99 (86, 118) kg; body mass index (BMI) 33 (29, 38) kg/m²; HbA1c 61 (54, 69) mmol/mol/(7.7 (7.1, 8.5) %). Data were collected at baseline and after 3, 6 and 12 months of semaglutide treatment. Data were analysed using a general linear mixed model for repeated measurements. Results: After 12 months, the reductions in HbA1c were (mean [95% confidence interval]: GLP‐1RA naïve: −12.8 [−17.0, −8.5] mmol/mol/ −1.2 [−1.6, −0.8]% ( p < 0.01) and GLP‐1RA experienced: −6.4 [−9.0, −3.8] mmol/mol/ −0.6 [−0.8, −0.4]% ( p < 0.01), respectively. Body weight reductions in GLP‐1RA naïve: −5 [−6.9, −3.1] kg ( p < 0.01) and GLP‐1RA experienced: −3.2 [−4.4, −2.0] kg ( p < 0.01), respectively. Seventy‐five percent received 1 mg QW semaglutide. Conclusion: We observed effects of semaglutide once weekly on HbA1c and body weight comparable with the effects observed in clinical studies with fewer persons in our cohort receiving maximum dose of semaglutide.